Organização, participação política e demandas indígenas para a política de assistência social em processos conferencistas - Niedermayer, Natália Raquel (2021)
This research starts from investigations arising from the theme of the rights of indigenous peoples and seeks, from theoretical knowledge already systematized as well as university and external activities with indigenous peoples, to understand and unravel the main problem that instigates the production of this work, the insertion of these peoples in institutions of democratic participation, especially at conferences, and identify indigenous demands for social assistance policy. To achieve these goals, we approach central categories such as the historical process of construction of the rights of indigenous peoples, contemplating their movements and social organizations that act in an affective way in the defense of their rights and territories. More generally, we present some considerations about the concept of participation in Brazil and its main challenges, with greater emphasis on conferences. Regarding the indigenous theme, we analyzed the construction of participatory spaces for indigenous peoples in Brazil, with emphasis on the first and second National Conference of Indigenous Peoples and the first National Conference on Indigenous Policy. We consider these meetings to be fundamental to understanding the capacity for organization and mobilization of indigenous peoples. In addition to these meetings, we analyzed the reports provided by the Municipal Council of Guaíra and the State and National Councils for Social Assistance. In these reports, we seek to identify the demands related to indigenous peoples and whether there was an active participation of these subjects in these meetings. In order to situate the municipal demands in Guaíra, specifically from the Guarani people, we carried out a historical review of the process of colonization and territorial dispossession that took place in western Paraná in order to better understand the current determinations of traditional territories, occupations and political organization of this people. In this way, we affirm that it is extremely important to strengthen indigenous organizations and their participatory and deliberative spaces so that they can advance in meeting their demands for this policy in a specific way. Finally, we emphasize that the greatest demand historically has been the defense of traditional territories, and it is essential to demarcate this position in all spaces where the rights of these peoples are discussed.